Importance of ultrasound evaluation at 11+0 - 13+6 weeks of pregnancy. An update - Nazario-Redondo, Conny Nazario-Redondo (2011)
First trimester ultrasound scan (11+0 to 13+6 weeks) is currently one of the most important clinical tools in managing pregnant women and their fetuses. It represents the best example of screening in Obstetrics to assess risk for chromosomal abnormalities and combined with maternal and obstetrical characteristics could be a useful predictor of obstetrical complications. We aim to present comprehensive summary of this important topic in Fetal Medicine for people involved in providing maternal and perinatal care, i.e. obstetricians, midwives and parents.